Unexpectedly frequent occurrence of very small repeating earthquakes (−5.1 ≤ Mw ≤ −3.6) in a South African gold mine: Implications for monitoring intraplate faults. Issue 12 (23rd December 2015) - Naoi, Makoto; Nakatani, Masao; Igarashi, Toshihiro; Otsuki, Kenshiro; Yabe, Yasuo; Kgarume, Thabang; Murakami, Osamu; Masakale, Thabang; Ribeiro, Luiz; Ward, Anthony; Moriya, Hirokazu; Kawakata, Hironori; et al.
Abstract: We observed very small repeating earthquakes with −5.1 ≤ Mw ≤ −3.6 on a geological fault at 1 km depth in a gold mine in South Africa. Of the 851 acoustic emissions that occurred on the fault during the 2 month analysis period, 45% were identified as repeaters on the basis of waveform similarity and relative locations. They occurred steadily at the same location with similar magnitudes, analogous to repeaters at plate boundaries, suggesting that they are repeat ruptures of the same asperity loaded by the surrounding aseismic slip (background creep). Application of the Nadeau and Johnson (1998) empirical formula (NJ formula), which relates the amount of background creep and repeater activity and is well established for plate boundary faults, to the present case yielded an impossibly large estimate of the background creep. This means that the presently studied repeaters were produced more efficiently, for a given amount of background creep, than expected from the NJ formula. When combined with an independently estimated average stress drop of 16 MPa, which is not particularly high, it suggests that the small asperities of the presently studied repeaters had a high seismic coupling (almost unity), in contrast to one physical interpretation of the plate boundary repeaters. The productivity of such repeaters, per unit background creep, is expected to increase strongly as smaller repeaters are considered (∝ Mo −1/3 as opposed to Mo −1/6 of the NJ formula), which may be usable to estimate very slow creep that may occur on intraplate faults. Key Points: The smallest repeating earthquakes ever identified as such on geological faults They are likely repeat ruptures of asperities induced by creep of the surrounding fault They repeated much more frequently than those at plate boundaries for a given amount of creep